Government Accounting Standards Application, HR Competence and Accounting Information Systems Influence on Financial Report Quality - Lawita, Florencia Irena; Iskandar, Donant Alananto (KALBISCIENTIA Jurnal Sains dan Teknologi, 2024)
This study aims to prove the effect of Budgeting Participation Influence, Budget Targets Clarity, and Public Accountability on the Performance of Local Government Agencies (Empirical Study in DKI Jakarta Province). The results of this study indicate that the Government Accounting Standards and Government Human Resources Competence do not have a significant positive effect on the quality of local government financial reports. The increase or standard of government accounting will have a significant impact on the quality of local government financial reports, seen from the respondents' level of education most of them are not accounting majors whose staff work in the finance or accounting department is more than 50% of the number of respondents. While the Accounting Information System Technology has a positive and significant effect on the quality of financial statements. This is because the accounting information system technology that is increasingly developing will be able to assist the process of preparing financial statements which are certainly more effective and efficient.